Pelatihan Kewirausahaan Pembuatan Costume Case Character Dalam Meningkatkan Pendapatan Masyarakat Di Kota Pekanbaru - Ainun Mardiah; Herlinda herlinda; Desvi Emti; Sehani Sehani; Ratna Dewi; Sofiyanita Sofiyanita (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service activity aims to provide knowledge to the community regarding the process of making costume case characters that can be used as entrepreneurial opportunities for the community in Pekanbaru City. This activity was held in Pekanbaru City on June 19, 2021. The training participants were housewives and teenagers in Tangkerang Barat Village with a total of 15 trainees. The method of community service activities uses lecture and demonstration methods about making costume case characters. The evaluation design for service activities is the achievement of the target number of training participants, the training objectives are well achieved, the planned material targets are achieved and the participants are able to understand the training material. The result of this service activity is that the participants understand the entrepreneurial opportunities of making costume case characters and training participants can make costume case characters.